2015
DOI: 10.1016/j.phytol.2014.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids from the roots of Stemona javanica (Kunth) Engl. (Stemonaceae) and their anti-malarial, acetylcholinesterase inhibitory and cytotoxic activities

Abstract: . Alkaloids from the roots of Stemona javanica (Kunth) Engl. (Stemonaceae) and their anti-malarial, acetylcholinesterase inhibitory and cytotoxic activities. Phytochemistry Letters, Alkaloids from the roots of Stemona javanica (Kunth) Engl. (Stemonaceae) and their anti-malarial, acetylcholinesterase inhibitory and cytotoxic activities AbstractTwo new protostemonine-type alkaloids, javastemonine A and B (3 and 4) have been isolated from the root extracts of Stemona javanica together with four known Stemona alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…The IC 50 of croomine to the DHFR was 5.29 μ M, while tuberostemonine was not active to the enzyme [ 17 ]. Ramli et al (2015) reported that isoprotostemonine and javastemonine A have low to in active against multidrug resistant K1CB1 and wild type and antifolate strains of P. falciparum parasites in vitro [ 20 ]. On the other hand, isoprotostemonine and javastemonine A showed negative inhibition and they accelerated FNR reaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The IC 50 of croomine to the DHFR was 5.29 μ M, while tuberostemonine was not active to the enzyme [ 17 ]. Ramli et al (2015) reported that isoprotostemonine and javastemonine A have low to in active against multidrug resistant K1CB1 and wild type and antifolate strains of P. falciparum parasites in vitro [ 20 ]. On the other hand, isoprotostemonine and javastemonine A showed negative inhibition and they accelerated FNR reaction.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, isoprotostemonine and javastemonine A showed negative inhibition and they accelerated FNR reaction. The javastemonine A exhibited moderate activities against P. falciparum TM4 and KI strains with IC 50 of 17.7 and 16.8 ppm, respectively [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(11Z )-1 ′ ,2 ′ didehydrostemofoline displayed the strongest larvicidal activity with a LC50 value of 2.44 mM. In a study reported by Ramli et al, 61 3 alkaloids including 13-demethoxy-11(S*), 12(R*)-dihydroprotostemonine, isoprotostemonine, and protostemonine exhibited moderate antiplasmodial activities against the Plasmodium falciparum strains, TM4 (IC 50 values of 17.7 3.7, 16.8 5.4, and 16.0 4.2 mg/mL, respectively) and K1 (IC 50 values of 16.8 3.1, 14.1 3.7, and 11.9 3.3 mg/mL, respectively).…”
Section: Other Bioactivitiesmentioning
confidence: 92%
“…Isoneostemocochinine- N -oxide ( 96 ) and neostemocochinine- N -oxide ( 97 ), 2 alkaloids with an N-oxide group, were achieved from the roots of Stemona cochinchinensis (Figure 4). 60 Ramli et al 61 separated and identified javastemonines A ( 98 ) and B ( 99 ) from the root extracts of Stemona javanica (Figure 4). These compounds have a lactone ring attached to C11.…”
Section: Phytochemistrymentioning
confidence: 99%